Catfish Business Development Strategy (Clarias Batrachus) On Fairy Catfish In Bengkulu City - Giri Asvian Putra; Ana Nurmalia; Herri Fariadi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose:”Identification of internal and external factors in the Peri business and catfish development strategies in Bengkulu City aims to increase business income. Methodology: This research is qualitative with a descriptive approach, which applies SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) analysis, as well as IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) analytical methods. Results:The research on the catfish business development strategy in Bengkulu City revealed that the main strength factors are the high nutritional content and the high production volume (score 0.57).” The main weakness factor is the low quality of the ponds (score 0.20), and the total weighted score for the Internal Factor Evaluation (IFE) Matrix is 2.78. Findings: The main opportunity factor is the high market demand (score 0.58), the main threat factor is the market distance (score 0.26), and the total weighted score for the External Factor Evaluation (EFE) Matrix is 2.72. Novelty: This research presents a comprehensive approach by integrating SWOT analysis with the IFAS and EFAS matrices within the context of the catfish farming business in Bengkulu City, which has rarely been applied before. This approach simultaneously combines the quantitative and qualitative evaluation of internal and external factors, while formulating strategies based on concrete field data. Originality: The development of the catfish business as a local commodity, considering nutritional, production, and digital marketing aspects (which are still minimally implemented), and the use of IFAS and EFAS analysis in processing SWOT data, provides a new perspective for relevant and applicable development strategies for catfish farming entrepreneurs. Conclusion: The catfish farming business development strategy resulted in six (6) alternative strategies, namely:1) Increasing market demand and production. 2) Socializing the high nutritional content to attract consumers. 3) Expanding the distribution network. 4) Enhancing consumer appeal by prioritizing catfish size. 5) Utilizing digital marketing technology such as social media to promote catfish in the sales market. 6) Developing derivative processed products based on catfish. Type of Paper: A research article with a descriptive qualitative approach focusing on business development strategy analysis.